PP.05.06: LEPTIN AND HEART RATE IN SUBJECTS WITH LOW CARDIOVASCULAR RISK. (June 2015) - Ivkovic, V.; Kos, J.; Karanovic, S.; Lela, I. Vukovic; Premuzic, V.; Dika, Z.; Laganovic, M.; Pecin, I.; Fucek, M.; Simicevic, L.; Sertic, J.; Vrdoljak, A.; et al.
Abstract : Objective: Several studies showed that leptin may be associated with faster heart rate (HR) and it was questioned whether this could be associated with increased cardiovascular risk. Our goal was to examine the possible association of leptin and HR in subjects with low cardiovascular risk. Design and method: Participants (N = 208; 135 females; 137 normotensives, 34 prehypertensives and 37 untreated hypertensives) were selected from a random sample of 2487 subjects enrolled in an observational study. Subjects with diabetes, chronic kidney disease, pregnancy, terminal illness and treated hypertensives were excluded. BP was measured using Omron M6 device following ESH/ESC guidelines. Leptin concentration was determined by ELISA. Results: In the whole group leptin concentration was higher (12.10 (6.12–17.50) vs. 4.01 (1.70–8.17), p < 0.001) in women than in men. There were no significant differences in leptin concentrations between normotensives (NT), prehypertensives (PHT) and untreated hypertensives (uHT). However, uHT (11.20 (6.00–16.90)) had significantly higher leptin concentration than NT (8.60 (3.60–14.65);p < 0.05) and non-significantly higher than PHT (8.04 (3.60–12.60;p > 0.05)). There were no differences between NT and PHT (p > 0.05). HR was similar in all three BP groups (p = 0.82). Leptin was positively correlated with BMI, albuminuria, CRP and insulin concentrations (p < 0.05). HR was positively correlated with eGFR and insulin and negatively with HDL. There were no significant correlations of leptin and HR in any of three BP groups. In multivariate analysis leptin was not a significant predictor of HR (Beta = -0.01, p = 0.90), systolic (Beta = -0.06, p = 0.27) or diastolic BP (Beta = 0.03, p = 0.58). BMI and female sex were positively associated with leptin concentration in multivariate analysis (p < 0.05). Conclusions: In our group of subjects with low cardiovascular risk leptin was not associated with HR. Hypertensive patients had higher leptin concentrations than NT and non-significantly higher than PHT subjects, latter two having similar leptin concentrations.